Pelaksanaan Program Literasi dan Numerasi dalam Kerangka Kurikulum Merdeka di Sekolah Dasar - Kartono, Kartono; Ghasya, Dyoty Auliya Vilda; Johan, Gio Mohamad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research attempts to describe several things including, (1) design of literacy and numeracy programs in elementary schools, (2) implementation of literacy and numeracy programs, (3) supporting factors for literacy and numeracy programs and (4) obstacles in implementing numeracy literacy programs. This study used descriptive qualitative method. The research results obtained include; (1) the design of the literacy and numeracy program at SD Negeri 17 Pontianak Kota District is generally carried out by adapting to the content related to literacy and numeracy contained in the independent curriculum and the 2013 curriculum which is currently being implemented in schools; (2) the results of the implementation of the literacy program have been implemented in 3 ways, namely habituation, learning and development; (3) supporting factors come from program targets and the government which helps facilitate literacy and numeracy programs, and (4) obstacles found in the form of low interest in reading and writing among literacy and numeracy program targets in schools. Thus, literacy and numeracy programs need to be implemented with various preparations and considerations so that they can run optimally for students and are of course in line with the applicable curriculum.